Synthesis of Imidazo[1, 2‐a]pyridines and Imidazo[2, 1‐b]thiazoles Attached to a Cycloalkyl or Saturated Heterocycle Containing a Tertiary Hydroxy Substitution. (1st April 2019) - Chenna Reddy, M. L.; Patil, Vineetkumar B.; Nawaz Khan, Fazlur Rahman; Saravanan, Vadivelu
Abstract : A new method has been developed for the synthesis of imidazo[1, 2‐ a ]pyridines, imidazo[2, 1‐ b ]thiazoles, and benzo[ d ]imidazo[2, 1‐ b ]thiazoles attached to a cycloalkyl or saturated heterocycle containing a tertiary hydroxy substitution. Readily available substituted 2‐aminopyridines, 2‐aminothiazoles, and 2‐aminobenzothiazoles were treated with bromohydroxycycloalkyl ethanones to afford the desired products in good yields. Abstract :